Sodium-copper hexacyanoferrate-functionalized magnetic nanoclusters for the highly efficient magnetic removal of radioactive caesium from seawater. (15th November 2017) - Yang, Hee-Man; Hwang, Kyu Sun; Park, Chan Woo; Lee, Kune-Woo
Abstract: Sodium-copper hexacyanoferrate (NaCuHCF)-functionalized magnetic nanoadsorbents were fabricated for the highly efficient magnetic removal of radioactive caesium from seawater. The magnetic nanoclusters (MNCs), composed of many individual Fe3 O4 nanoparticles, were covalently coated with polyethyleneimine (PEI) to functionalize the MNC surfaces with NaCuHCF. After simple immobilization of Cu and Na ferrocyanide on the NC surface, the resulting NaCuHCF-functionalized MNCs showed good magnetic properties and a significant adsorption capacity for Cs + with a high content of NaCuHCF (36.04%). The adsorption kinetics and isotherms were well fit to a pseudo-second-order model and Langmuir isotherm, respectively. The sorption of 97.35% Cs by the NaCuHCF-PEI-MNCs completed in less than 5 min, and the maximum adsorption capacity of the adsorbent was 166.67 mg/g. The NaCuHCF-PEI-MNCs selectively adsorbed Cs even in the presence of various competing ions, such as Na, K, Mg, and Ca, and the Cs removal mechanism was revealed as ion exchange between Cs in solution and Na in the NaCuHCF-PEI-MNCs. In radioactive tests, our adsorbent displayed excellent removal performance in real seawater with a high removal efficiency exceeding 99.73%, a decontamination factor exceeding 372, and a high stability in water over a wide pH range from 4 to 10 with negligible leaching of Fe. Graphical abstract: Highlights: Sodium-copper hexacyanoferrate-functionalized magnetic nanoclusters were prepared. They have an excellent adsorption capacity with good selectivity to Cs. They show good colloidal stability over a wide pH range. The magnetic adsorbents could be separated rapidly by an external magnetic field. Our adsorbent displayed excellent removal performance in real seawater.